Business sustainability for competitive advantage: identifying the role of green intellectual capital, environmental management accounting and energy efficiency. Issue 2 (10th July 2023) - Jiao, Xiaojing; Zhang, Pengwei; He, Liying; Li, Zeyun
Abstract: The manufacturing organizations are threatening the earth and its wildlife because of their growing concern about environmental pollution and industrial waste. Hence, in the present study, the three potential solutions, Green Intellectual Capital, Environmental Management Accounting and Energy Efficiency, are evaluated for excelling the organizational operations towards business sustainability and attaining the Competitive Advantage. With the assistance of 'Partial Least Square-Structural Equation Modelling' on the dataset of 364 respondents from the manufacturing organizations in China, the outcome reported the positive and significant impact of all of the studied potential solutions in excelling and enhancing business sustainability and competitive advantage. Based on the findings, it is proposed that manufacturing organizations need to apportion due attention to developing the green intellectual capital, improve the level of consumption of energy and need to disclose their environmental management through proper Environmental Management Accounting.